PROPHETIC MEDICINE AND HERBS IN ORAL CARE A REVIEW OF LITERATURE - Hashmi, Arshee (International Journal of Islamic and Complementary Medicine, 2024)
Prophetic medicine comprises the teaching of the prophet Mohammad with regards to nutrition, hygiene, sickness, cure and prevention of the ailments. “Whenever the Prophet (ﷺ) would visit an ill person, he would said:‘[O Allah,] make the harm go away, Lord of mankind, and heal him, You are the Healer, there is no healing except your healing, a healing that does not leave any sickness. Healing with the Medicine of the Prophet (PBUH)  is the remedy for well-being, good health and soul. Prophetic medicines promote healing, prevention and cure of ailments. The review article is an effort to explore detailed analysis of prophetic medicines and natural herbs in oral care. The article is focused on the uses of miswak, honey, black seed, olives, senna and idhkhir for oral therapeutic uses. The studies, experiments and research have demonstrated that the prophetic medicines and herbs provide benefits in oral care. However, the research conducted on some herbs are limited to in vitro studies, thus further studies are required to be carried out on  animals  or humans to achieve accurate results. Furthermore, other herbs mentioned in prophetic medicines like tannumah (aloes), daghabis (dill seed), dates, cortus, need to be explored and further studied for therapeutic use in oral care.